1997
DOI: 10.1088/0741-3335/39/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Ion-acoustic waves in a multicomponent plasma with negative ions

Abstract: Propagation of ion-acoustic waves has been investigated experimentally in an argon plasma mixed with sulfur hexafluoride using a multidipole double-plasma device. The device is separated into a driver and a target section with a magnetic filter. Waves are transmitted by a circular mesh grid placed in the target. Both the fast and the slow modes were observed to propagate downstream in the wide range of the density ratio of negative ions to positive ions. The measured phase velocities are in agreement with theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 10 publications
(24 reference statements)
1
50
0
Order By: Relevance
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Negative ions have been detected in the Earth's ionosphere [18], cometary comae [19], and the upper regions of Titan [20]. Moreover, multicomponent plasmas, such as Ar/SF 6 and K/SF 6 plasmas, are generally used to perform basic research on IASWs in dc discharge devices and Q-machines [21][22][23][24][25][26][27][28]. Since the early space observations [29], it has been admitted that the Maxwellian distribution is not always a realistic distribution [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…We seek the stationary soliton-like solutions of the generalized KdV equation (17) cosh(χ/∆) , (19) where ∆ = 4y 3 /v 0 .…”
Section: Deviation From Isothermalitymentioning
confidence: 99%
“…Very recently many authors have studied the nonlinear propagation of ion-acoustic (IA) solitary waves (SWs) [1][2][3][4] dust-ion-acoustic (DIA) SWs [5][6][7][8][9], dust-acoustic (DA) SWs [10][11][12][13][14] in a multi-ion plasmas, as negative ions can be found in space [15,16] and laboratory [17][18][19] as well as positive ions. In multi-ion plasmas, there exist fast and slow mode.…”
Section: Introductionmentioning
confidence: 99%